(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The ability of bacteria to sense and respond to their surrounding allows them to survive and grow under different types of stressful conditions. Resistance, tolerance, and persistence are survival strategies Bacteria possess to overcome stressful environment. The failure of Antibiotic treatments is attributed to these defense strategies. The misclassification of these three phenotypes as a result of poor characterization can result in treatments ineffectiveness. Unlike resistance, which is resulted from evolutions or mutations and external resistant genes acquisitions, that allows bacteria to reproduce under antibiotics, persistence allows a subpopulation of susceptible bacteria to escape antibiotic stress by entering a dormant non-replicative state. Several molecular mechanisms have been reported to implicate bacterial persistence to antibiotics. The two most substantial mechanisms of persistence in bacteria are Toxin- antitoxin system and stringent response. This review summarizes the role of some molecular mechanisms (Stringent response, SOS response, Phosphate metabolism, Sigma factor, and Toxin- antitoxin system) in bacterial persistence.